Dermoscopic Patterns in Juvenile Xanthogranuloma Based on the Histological Classification - Xu, Jiaosheng; Ma, Lin (Frontiers in Medicine, 2021)
Several dermoscopic features of juvenile xanthogranuloma (JXG) have been previously described in single cases or small case series. We aimed to investigate the dermoscopic patterns of JXG in a large case series and the correlations of these with clinical features of different histopathological subtypes. Patients who underwent dermoscopic evaluation and had a histopathological diagnosis of JXG were recruited. Histological findings, including stage and Ki67 proliferative index and the dermoscopic features of each lesion were recorded. Forty-one patients with JXG were included. The male to female ratio was 1.28: 1 and the median age of onset was 11 months (range: 0-95 months). Fourteen lesions were histologically categorized in the early stage, 17 in the developed stage, and 10 in the late stage. The ‘setting sun’ pattern was observed in 35 lesions (85.4%) and ‘clouds’ of paler yellow areas in 26 lesions (63.4%). The frequency of the ‘setting sun’ pattern was higher in the early and developed stages (30/31) than in the late stage (5/10) (P=0.002), while that of ‘clouds’ of paler yellow areas was not significantly different between each stage. Branched linear vessels were detected in the early (11/14) and developed stage (6/17), but not in the late stage. The mean Ki67 index of the lesions with linear vessels was 11.8% (range: 2-40%), which was higher than that of lesions without linear vessels (mean index: 5%, range: 1-30%) (P=0.005). The pigment network and whitish areas were only detected in 6 and 5 lesions in the late stage, respectively. The whitish areas presented either as streak or stellate shape. The pigment network exhibited either in a centric or a peripheral pattern. The ‘setting sun’ pattern is the characteristic dermoscopic features of JXG in the early and developed stages, while whitish areas and pigment network are the characteristic patterns in the late stage. Linear vessels present as branched patterns and mostly occur in the early stage with a high proliferative index, indicating rapid growth. The whitish areas and pigment network may present in various patterns. Dermoscopy is a useful adjunctive tool in the diagnosis and staging of JXG.